Penilaian Pelaksanaan Program Pengembangan (Kajian Kes di Jabatan Pertanian Negeri Kedah) - Alyonner, Win Alfiandi (2013)
Agriculture Expansion Service Activities is the main activity of the Department of Agriculture. Expansion Service Activities is a method for distributing information and technology to farmers and entrepreneur. Therefore, this study was carrying out to evaluate the practices and activities of Agriculture Expansion Service by the Kedah Department of Agriculture. This was a qualitative study with face to face interview and discussion of some experts’ persons related to the Agriculture Expansion Service Program. In addition, analysis of secondary data was also performed to get accurate information. SWOT analysis is used to evaluate the implementation of Agriculture Expansion Service Program. From the results of interviews and discussions nine internal and nine external factors were identified. SWOT analysis found that Agriculture Expansion Service Program had higher scores factor in strength and opportunities compared to scores factor in weaknesses and threat. This proves that the Agriculture Expansion Program have high potential to increase the agricultural productivity in Kedah. Meanwhile, the TOWS Matrix recommended an integrated Agriculture Expansion Program was able to strengthen the implementation of agriculture expansion activities in Kedah.